2015
DOI: 10.1007/978-81-322-2473-0_13
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Chemistry, and Medical Application of Bacterial Cellulose Nanocomposites

Abstract: Bacterial cellulose (BC), an environmental friendly polymeric material, has recently received immense attention in the human society. Herein, we have focused on the biosynthesis, chemical structure, and physiological behavior of BC along with synthetic routes and medical applications of its nanocomposites. The structure of BC consists of nanofibrils made up of (1 → 4) β-glycosidic linked glucose units interconnected through intra-and intermolecular hydrogen bonds. The interconnected 3D network structure of BC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 153 publications
(202 reference statements)
0
15
0
Order By: Relevance
“…Large scale production for the commercial application requires BC with optimum shape, composition and maximum BC properties 17,42,43 . BC secretes as a pellicle under shaking condition or as a sheet at air-liquid interface in static culture 41,[44][45][46] . Advanced techniques for the fabrication of biomolecules using microbial cellulose are in progress and the cell-free system is one such technique 47,48 .…”
Section: Cultivation Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Large scale production for the commercial application requires BC with optimum shape, composition and maximum BC properties 17,42,43 . BC secretes as a pellicle under shaking condition or as a sheet at air-liquid interface in static culture 41,[44][45][46] . Advanced techniques for the fabrication of biomolecules using microbial cellulose are in progress and the cell-free system is one such technique 47,48 .…”
Section: Cultivation Techniquesmentioning
confidence: 99%
“…Decreased productivity and increased cultivation time limit industrial application of this culture technique. Pellicle formation is influenced by the surface of the culture medium, and also aeration at the vacuum/liquid interface will yield high-quality cellulose 44,49,50 . A newly invented bioreactor system, Horizontal Lift Reactor (HoLiR) was developed for semi-continuous production of BC.…”
Section: Static Cultivation Technique For Bc Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…It possesses unique structural, physico-chemical, mechanical, thermal, and biological features and is a Generally Recognized As Safe (GRAS) biological product (Yang et al, 2018;Zhong, 2020). It has been extensively used for various biomedical and other applications in the form of hydrogels, membranes, particles, and three-dimensional (3D) scaffolds, where its properties are tuned according to the target applications (Ul- Islam et al, 2015). Its innate features are modulated through the development of its composites with different materials like natural and synthetic polymers (Shah et al, 2013), nanomaterials (Ul- Khan et al, 2015;Ullah et al, 2016b), peptides (Curvello et al, 2019), ceramics (DeMello, 2012), clays (Ul- Islam et al, 2013a), plant extracts (Fatima et al, 2021;Ul-Islam et al, 2021a), and others (Mbituyimana et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the development of BNC-based wound dressings is currently on the market, while some BNC implants are in the phase of clinical studies as a novel solution to yet unresolved complications in regenerative medicine (Klemm et al, 2018;Sharma and Bhardwaj, 2019;Zhong, 2020). Studies have shown that the BNC-based scaffolds play vital roles in the regeneration of bone and cartilage (Khan et al, 2020a), as the drug delivery systems (Pachuau, 2017;Li et al, 2018), biosensing platforms (Jasim et al, 2017;Farooq et al, 2020), diagnostic tools (Ul- Islam et al, 2019b), and several other areas (Islam et al, 2015;Derakhshanfar et al, 2018;McCarthy et al, 2019a,b, Wang et al, 2020a. The impregnation of nanomaterials to BNC and its use as the wound dressing biomaterial, broad-spectrum antimicrobial, surface disinfectant, and nanodrugs for the treatment of different diseases (Lin and Dufresne, 2014;Di et al, 2017;Wang et al, 2020b) could be an effective approach for addressing several clinical issues.…”
Section: Introductionmentioning
confidence: 99%